Impact of considering non-occupational radiation exposure on the association between occupational dose and solid cancer among French nuclear workers. Issue 3 (21st October 2017) - Fournier, Lucie; Cléro, Enora; Samson, Eric; Caër-Lorho, Sylvaine; Laurier, Dominique; Leuraud, Klervi
Abstract : Objectives: The French nuclear worker cohort allows for the assessment of cancer risk associated with occupational radiation exposure, but workers are also exposed to medical and environmental radiation which can be of the same order of magnitude. This study aims to examine the impact of non-occupational radiation exposures on the dose-risk analysis between occupational radiation exposure and cancer mortality. Methods: The cohort included workers employed before 1995 for at least one year by CEA, AREVA NC or EDF and badge-monitored for external radiation exposure. Monitoring results were used to calculate occupational individual doses. Scenarios of work-related X-ray and environmental exposures were simulated. Poisson regression was used to quantify associations between occupational exposure and cancer mortality adjusting for non-occupational radiation exposure. Results: The mean cumulative dose of external occupational radiation was 18.4 mSv among 59 004 workers. Depending on the hypotheses made, the mean cumulative work-related X-ray dose varied between 3.1 and 9.2 mSv and the mean cumulative environmental dose was around 130 mSv. The unadjusted excess relative rate of cancer per Sievert (ERR/Sv) was 0.34 (90% CI −0.44 to 1.24). Adjusting for environmental radiation exposure did not substantially modify this risk coefficient, but it was attenuated by medical exposure (ERR/Sv point estimate between 0.15 and 0.23). Conclusions: Occupational radiation risk estimates were lower when adjusted for work-related X-ray exposures. Environmental exposures had a very slight impact on the occupational exposure risk estimates. In any scenario of non-occupational exposure considered, a positive but insignificant excess cancer risk associated with occupational exposure was observed.